2019
DOI: 10.3389/fphar.2019.00735
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo Flavonol Glycosides or Ginkgolides Tend to Differentially Protect Myocardial or Cerebral Ischemia–Reperfusion Injury via Regulation of TWEAK-Fn14 Signaling in Heart and Brain

Abstract: Shuxuening injection (SXNI), one of the pharmaceutical preparations of Ginkgo biloba extract, has significant effects on both ischemic stroke and heart diseases from bench to bedside. Its major active ingredients are ginkgo flavonol glycosides (GFGs) and ginkgolides (GGs). We have previously reported that SXNI as a whole protected ischemic brain and heart, but the active ingredients and their contribution to the therapeutic effects remain unclear. Therefore, we combined experimental and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 89 publications
0
22
0
Order By: Relevance
“…A standardized Ginkgo biloba extract 761 (EGb 761) has been used as strong antioxidative and neuroprotective agent to treat neurodegenerative diseases [21]. Furthermore, several researches have indicated that EGb 761 protects against renal, myocardial, and cerebral ischemiareperfusion injury [22][23][24][25], and improves hepatic DNA damage and liver microcirculation after warm ischemia [26,27]. Ginkgo biloba Dropping Pill (GBDP) is a unique Ginkgo biloba leaf extract preparation produced in China for treating angina pectoris and cerebral infarction caused by blood stasis.…”
Section: Introductionmentioning
confidence: 99%
“…A standardized Ginkgo biloba extract 761 (EGb 761) has been used as strong antioxidative and neuroprotective agent to treat neurodegenerative diseases [21]. Furthermore, several researches have indicated that EGb 761 protects against renal, myocardial, and cerebral ischemiareperfusion injury [22][23][24][25], and improves hepatic DNA damage and liver microcirculation after warm ischemia [26,27]. Ginkgo biloba Dropping Pill (GBDP) is a unique Ginkgo biloba leaf extract preparation produced in China for treating angina pectoris and cerebral infarction caused by blood stasis.…”
Section: Introductionmentioning
confidence: 99%
“…Ginkgolide B stimulated the proliferation and differentiation of neural stem cells in the in vivo models of NSCs in the rat brain following cerebral ischemia, thereby increasing the proportion of neurons to improve neurological outcomes [102]. Ginkgolide B is a potential neuro-protectant and in a study, the cellular and molecular mechanisms were dissected out by following the BDNF, EGF, and Suppressor of cytokine signaling 2 (SOCS2) [185]. Another phytochemical, curcumin, extensively studied shows beneficial effect in case of stroke too.…”
Section: Vascular Cognitive Impairmentmentioning
confidence: 99%
“…GK, a derivate of GB, given at a higher dose also attenuated cerebral infarction and repressed brain edema formation in MCAO rats (Ma et al 2012). In a cerebral ischemia-reperfusion injury (CIRI) model, pretreatment with Ginkgolides at 2.5 ml/kg reduced cerebral infarction area and cerebral edema, partly through TWEAK–Fn14 cytokine receptor axis (Xiao et al 2019). The effect of bilobalide on brain edemas has been demonstrated in animal experiments.…”
Section: Mechanisms Of Ginkgolides and Bilobalide In Neuron Protectiomentioning
confidence: 99%